Awareness about rabies among general population and treatment seeking behaviour following dog-bite in rural Puducherry: a community based cross-sectional study - Krishnamoorthy, Yuvaraj; M., Vijayageetha; Sarkar, Sonali (International Journal Of Community Medicine And Public Health, 2018)
Background: India contributes to one-third of rabies death globally. Despite the efforts taken by government, Rabies incidence in India has been constant for over a decade. Hence, there is need to assess the awareness and treatment-seeking behaviour which will help to plan strategies to prevent rabies related deaths. The objective of the study was to assess the awareness about rabies among general population and to determine the treatment-seeking behaviour and adherence to anti-rabies vaccine among victims of dog-bite in rural Puducherry Methods: Community based cross-sectional study was conducted during November 2016 in rural Puducherry. 386 individuals were covered in four villages. Information on socio-demographic characteristics and awareness regarding rabies, treatment-seeking behaviour and adherence to anti-rabies vaccine among dog-bite victims was collected using pre-tested questionnaire. Results: Among 386 participants, 244 (63.2%) were in the age group 31-60 years, 259 (67.1%) were females, 103 (26.7%) had no formal-education. About 68% were found to have adequate knowledge regarding rabies but only 49.5% were aware of local wound-management and 237 (61.4%) showed a positive attitude towards vaccination following scratches/lick over abraded skin. Among 27 (6.9%) with history of dog-bite in last one-year, 17 (62.9%) had taken first-aid measures. All 27 (100%) had visited hospital out of which 24 (88.8%) adhered to vaccination schedule. Conclusions: Although two-thirds of the study populations were found to have adequate knowledge regarding rabies, half of them had no knowledge regarding first-aid measures. Although all dog bite victims visited hospital, some did not adhere to the schedule mainly due to negligence. Hence, there is need to create awareness regarding wound management and post-exposure immunization.